2021
DOI: 10.1089/jpm.2020.0178
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a Clinic-Based Telehealth Support Service (FamilyStrong) for Family Caregivers of Individuals with Grade IV Brain Tumors

Abstract: Background: Nearly 3 million U.S. family caregivers support someone with cancer. However, oncology clinicbased service lines that proactively screen, assess, and support cancer caregivers are nearly nonexistent. Objective: To examine first-year experiences of a nurse-led clinic-based telehealth support service (Family-Strong) for family caregivers of patients with recently diagnosed grade IV brain tumors. Methods: This is a retrospective evaluation of operational outcomes from initial implementation of the Fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 17 publications
(20 reference statements)
0
29
0
Order By: Relevance
“…We found that we could increase scalability while maintaining high-quality support for family caregivers using a lay navigation model of telehealth support. Dionne-Odom and colleagues [42][43][44][45][46][47] developed Project ENABLE Cornerstone based on a series of studies examining cancer family caregivers' needs, especially in Black and rural underserved populations. In Cornerstone, trained lay navigators are overseen by specialist palliative care clinicians and provide family care partners with a series of brief in-person and telehealth sessions focusing on stress management and coping, caregiving skills and organization, getting help, selfcare, and preparing for the future/advance care planning.…”
Section: Providing Evidence-based Palliative Care Via Telehealthmentioning
confidence: 99%
“…We found that we could increase scalability while maintaining high-quality support for family caregivers using a lay navigation model of telehealth support. Dionne-Odom and colleagues [42][43][44][45][46][47] developed Project ENABLE Cornerstone based on a series of studies examining cancer family caregivers' needs, especially in Black and rural underserved populations. In Cornerstone, trained lay navigators are overseen by specialist palliative care clinicians and provide family care partners with a series of brief in-person and telehealth sessions focusing on stress management and coping, caregiving skills and organization, getting help, selfcare, and preparing for the future/advance care planning.…”
Section: Providing Evidence-based Palliative Care Via Telehealthmentioning
confidence: 99%
“…These weekly sessions were followed by monthly check‐in calls for 24 weeks to address any new or ongoing issues. All calls included caregiver distress screening, which we adapted in our prior work from National Comprehensive Cancer Network patient distress screening 21,26 . Coaches facilitated problem‐solving and goal‐setting support for caregivers who desired assistance with issues noted in distress screening 27 .…”
Section: Methodsmentioning
confidence: 99%
“…While one study of 600 stage IV cancer patients and 346 caregivers demonstrated that patients found communication with physicians to be well-executed compared to caregivers' opinions, both groups reported worse perceptions of physician communication and care coordination when anxious ( 105 ). Dionne-Odom et al examined outcomes following implementation of a clinic-based telemedicine support system (FamilyStrong) for caregivers of patients with grade IV brain tumors ( 106 ). A palliative care nurse interfaced with caregivers on a weekly basis, evaluating for distress and advocating for various support services, including local counseling services and coordinating with the primary neuro-oncology team for patient care needs.…”
Section: Role Of Multidisciplinary Care and Palliative/supportive Car...mentioning
confidence: 99%